PENGARUH DESENTRALISASI, PARTISIPASI ANGGARAN, INFORMASI ASIMETRI DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL PADA IKIP PGRI SEMARANG - Ambar Mulyani, 0835030726; Maryono, Maryono (Students Journal of Accounting and Banking, 2012)
The role is very big budget for managers, both at the time of the preparation of the work program, the current implementation, as well as assessment of the realization of the activities. Based on the background of problems that have been outlined in advance, it can be seen that the problems faced by IKIP PGRI Semarang is less optimal managerial performance, which is visible from the unit budget realization report showing that the budget set by the realization yet achieved optimally.This study aimed to examine the effect of decentralization, participatory budgeting, information asymmetry and organizational commitment on managerial performance in IKIP PGRI Semarang. In this study population was drawn line managers comprised of middle managers and managers IKIP PGRI Semarang low at 99 people, with a total sample size of 34 respondents. The analytical tool used in this study is Multiple Linear Regression Analysis, which previously tested the validity and reliability, as well as the classic assumption test normality. Decentralization on managerial performance showed a positive effect, meaning that if there is a match between decentralization is applied to the needs of decision-makers to support quality decision to be taken and may ultimately improve managerial performance in IKIP PGRI Semarang. Participation budgeting positive influence on managerial performance. Information asymmetry negatively affect managerial performance, means that the higher the asymmetry of information provided by the manager, the more it will degrade the performance of management. Positively influence organizational commitment on managerial performance is significantly positive.Kata Kunci: Desentralisasi, partisipasi anggaran, informasi asimetri, komitmen organisasi dan kinerja manajerial